Determinants and levels of cervical Cancer screening uptake among women of reproductive age in South Africa: evidence from South Africa Demographic and health survey data, 2016 - Monica Ewomazino Akokuwebe; Erhabor Sunday Idemudia; Abiel M. Lekulo; Ogone Warona Motlogeloa (BMC, 2021)
Abstract Background Cervical cancer (CC) is the cancer with the most incidents and the leading cause of cancer mortality among women in South Africa. CC screening is one of the most cost-effective control approaches for the disease burden. This study assessed the determinants and individual-level indicators of cervical cancer screening uptake among women of reproductive age in South Africa. Methods We analyzed data from the 2016 South Africa Demographic Health Survey. Our analysis focused on 5903 women (15-49 years). We conducted Chi-square test for bivariate analysis, and multivariate binary logistics regression was used to analyze independent association between individual-level factors and women who have had Pap smear testing. Statistical significance was set at p < 0.05. Results The mean age at cervical cancer screening uptake among women in South Africa was 40.8 years (SD 18.6, range 15-95 years). A majority of the women (39.3%) were aged 45 years and above and 54.6% of them resides in urban settlements. About 35.4% of women (n = 2098) have had a Pap smear test, with 66.5% of them who had a Pap smear test resides in Western Cape province. The proportion of women who had a Pap smear test was significantly higher among those with higher educational attainment (68.7%, p = 0.000), in the rich wealth index (50.1%, p = 0.000), and those with health insurance cover (60.3%, p = 0.000). Pap smear testing was found to be more prevalent among women aged 45+ years, were in the white population group, had higher education, were divorced, and had health insurance cover. The predominance of Pap smear test was 14% higher among women who are working in the professional/formal sector (AOR; 1.38, 95% CI; 1.14-1.69). The uptake of Pap smear test was also higher among women aged 35-44 years. Conclusions The prevalence of cervical cancer uptake is substantially low among women aged 15-24 years in South Africa and shows a degree of between-provinces differences. Therefore, heath educational interventions aimed at increasing the uptake of cervical cancer screening services in South Africa are critically needed.